Preoperative imaging for colorectal liver metastases: a nationwide population-based study. Issue 4 (6th May 2020) - Elfrink, A K E; Pool, M; Werf, L R; Marra, E; Burgmans, M C; Meijerink, M R; Dulk, M; Boezem, P B; Riele, W W; Patijn, G A; Wouters, M W J M; Leclercq, W K G; et al.
Abstract: Background: In patients with colorectal liver metastases (CRLM) preoperative imaging may include contrast-enhanced (ce) MRI and [ 18 F]fluorodeoxyglucose ( 18 F-FDG) PET–CT. This study assessed trends and variation between hospitals and oncological networks in the use of preoperative imaging in the Netherlands. Methods: Data for all patients who underwent liver resection for CRLM in the Netherlands between 2014 and 2018 were retrieved from a nationwide auditing database. Multivariable logistic regression analysis was used to assess use of ceMRI, 18 F-FDG PET–CT and combined ceMRI and 18 F-FDG PET–CT, and trends in preoperative imaging and hospital and oncological network variation. Results: A total of 4510 patients were included, of whom 1562 had ceMRI, 872 had 18 F-FDG PET–CT, and 1293 had combined ceMRI and 18 F-FDG PET–CT. Use of ceMRI increased over time (from 9·6 to 26·2 per cent; P < 0·001), use of 18 F-FDG PET–CT decreased (from 28·6 to 6·0 per cent; P < 0·001), and use of both ceMRI and 18 F-FDG PET–CT 16·9 per cent) remained stable. Unadjusted variation in the use of ceMRI, 18 F-FDG PET–CT, and combined ceMRI and 18 F-FDG PET–CT ranged from 5·6 to 100 per cent between hospitals. After case-mix correction, hospital and oncological network variation was found for all imaging modalities. Discussion: Significant variation exists concerning the use of preoperative imaging for CRLM between hospitals and oncological networks in the Netherlands. The use of MRI is increasing, whereas that of 18 F-FDG PET–CT is decreasing. Graphical Abstract: A nationwide population-based overview from 2014 to 2018 in the Netherlands showed an increased use of contrast-enhanced MRI and decreased use of PET–CT. There was significant hospital variation in the use of both MRI and PET–CT. Wide variation in the use of preoperative MRI and FDG-PET-CT